FEATURES OF THE FORMATION OF SOCIAL COMPETENCE OF FUTURE SPECIALISTS IN SOCIAL WORK DURING STUDENT PRACTICE - Макар, Людмила (SWorldJournal, 2021)
The article is devoted to the peculiarities of the formation of social competence of future social workers during their educational and industrial practice; the issues of the level of requirements for the competence of a specialist in the provision of soc